Ultrasonic treatment-assisted reductive deposition of Cu and Pd nanoparticles on ultrathin 2D Bi2S3 nanosheets for selective electrochemical reduction of CO2 into C2 compounds - Bilal Masood Pirzada; Faisal AlMarzooqi; Ahsanulhaq Qurashi (Ultrasonics Sonochemistry)
In this work, we have ultrasonically deposited Cu and Pd nanoparticles on Bi2S3 nanoparticles, prepared using an ultrasonication assisted hydrothermal method. We implemented intense ultrasonic waves bearing frequency of 20 kHz and power of 750 W at the acoustic wavelength of 100 mm to reduce Cu and Pd nanoparticles on the Bi2S3 surface. The XRD confirmed the formation of highly crystalline Bi2S3 nanoparticles with a pure orthorhombic phase and the deposition of copper (Cuo) and palladium (Pdo) nanoparticles was indicated by the strengthening and broadening of the peaks. XPS also confirmed the formation of Cuo and Pdo nanoparticles on Bi2S3. The Transmission Electron Microscopy (TEM) also exhibited the deposition of Cu and Pd nanoparticles on the Bi2S3 nanosheets which was further confirmed using high resolution TEM analysis. The electrochemical CO2 reduction by Cu-Pd/Bi2S3 electrocatalyst using Cu foam as the conducting support led to the formation of acetaldehyde and ethylene as the major products. The rate of formation of ethylene was found to be 488.5 μ mol g-1h−1 at an applied potential of −0.6 V (vs. RHE), with the best Faradaic efficiency of 57.09 % at −0.4 V (vs. RHE). Among the liquid phase products, acetaldehyde was the major product showing the maximum Faradaic efficiency of 6.473 % at −0.2 V (vs. RHE), with a total formation rate of 64.27 μ mol g-1h−1. The results revealed that the Cu-Pd/Bi2S3 electrocatalyst was more selective to C2 products while the pure Bi2S3 nanoparticles majorly produced C1 compounds.